2012
DOI: 10.1007/s10072-012-1080-3
|View full text |Cite
|
Sign up to set email alerts
|

Headache at high school: clinical characteristics and impact

Abstract: Although migraine (MH) and tension type headache (TTH) are the most common and important causes of recurrent headache in adolescents, they are poorly understood and not recognized by parents and teachers, delaying the first physician evaluation for correct diagnosis and management. The purpose of this study is to assess the knowledge about headache impact among the students of a Communication Private High School in Rimini city, and to evaluate the main different types of headaches interfering with school and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 17 publications
1
4
0
4
Order By: Relevance
“…Headaches affected the participants’ personal care and lifting of objects. This finding is consistent with that of other studies (Tonini and Frediani 2012 ). Students also report the fear of letting people down whilst experiencing headaches.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Headaches affected the participants’ personal care and lifting of objects. This finding is consistent with that of other studies (Tonini and Frediani 2012 ). Students also report the fear of letting people down whilst experiencing headaches.…”
Section: Discussionsupporting
confidence: 94%
“…In an American population, 51 % of the participants reported a decrease in school work and productivity by 50 % (Lipton et al 2001 ). In a secondary school in Italy, 92 % of headache sufferers had difficulty in paying attention to lessons, participation in afternoon sport and completing homework tasks given to them (Tonini and Frediani 2012 ). Migraine sufferers missed twice as many days of classes and suffered reduced quality of life (Smitherman et al 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…In our study, more than half of responders never consulted a physician for their headache, which was somewhat lower than in a similar study from Germany, as was the percentage of adolescents taking medication for their headache (9). A study from Italy showed that none of the adolescents suffering from headache had visited a doctor (26). A study from the United States showed that 40% of adolescents visited a health care provider and less than one in five reported taking medications to prevent headache (17).…”
Section: Discussionmentioning
confidence: 99%
“…The leading self-perceived triggers for headache, especially for migraine, among adolescents were stress, lack of sleep and too much school work (6,26,28,29). In contrast, the statistical analysis in another study identified alcohol and coffee consumption, smoking, neck pain, stress and physical inactivity as risk factors for headache (6).…”
Section: Discussionmentioning
confidence: 99%
“…(8) Prevalências próximas das encontradas em estudos recentes. (9)(10)(11)(12) Nesse sentido, esse estudo tem como objetivo analisar, através de uma revisão sistemática, a epidemiologia da cefaleia e sua associação com a qualidade de vida dos adolescentes. Tais resultados podem direcionar futuras intervenções que visem diminuir a incidência de cefaleia no público jovem.…”
Section: Introductionunclassified